Ultra-high performance fibre-reinforced concrete under impact: experimental analysis of the mechanical response in extreme conditions and modelling using the Pontiroli, Rouquand and Mazars model. (28th January 2017) - Erzar, Benjamin; Pontiroli, Christophe; Buzaud, Eric
Abstract : To evaluate the vulnerability of ultra-high performance fibre-reinforced concrete (UHPFRC) infrastructure to rigid projectile penetration, over the last few years CEA-Gramat has led an experimental and numerical research programme in collaboration with French universities. During the penetration process, concrete is subjected to extreme conditions of pressure and strain rate. Plasticity mechanisms as well as dynamic tensile and/or shear damage are activated during the tunnelling phase and the cratering of the concrete target. Each mechanism has been investigated independently at the laboratory scale and the role of steel fibres especially has been analysed to understand their influence on the macroscopic behaviour. To extend the experimental results to the structural scale, penetration tests on UHPFRC slabs have been conducted by CEA-Gramat. The analysis of this dataset combined with material characterization experiments allows the role of steel fibres to be identified in the different plasticity and damage mechanisms occurring during penetration. In parallel, some improvements have been introduced into the concrete model developed by Pontiroli, Rouquand and Mazars (PRM model), especially to take into account the contribution made by the fibres in the tensile fracture process. After a primary phase of validation, the capabilities of the PRM model are illustrated by performing numerical simulations of projectile penetration into UHPFRC concrete structures. This article is part of the themed issue 'Experimental testing and modelling of brittle materials at high strain rates'.